Impact of Relationship Marketing on Customer Loyalty in Online Retailing in Delhi-NCR - Alva, Brijesh R (Digital Repository of Theses, 2025)
The rapid expansion of online retailing in India has transformed the way consumers shop, creating both opportunities and challenges for businesses. This thesis focuses on the critical factors affecting customer loyalty for the emerging online retail sector in India with particular reference to some important relationship marketing dimensions such as personalization, trust, communication, concord, etc. This study aims at building theoretical and practical terms on how online retailers can create and maintain their customer relationship for sustainable ones relative to high competition. Structured questionnaire was employed for a deeper understanding of how customer loyalty takes form. Data collection has taken place in a very economically viable DelhiNCR region that boasts diversity in consumer demographic and behavior with regard to the e-commerce phenomenon in India. The structured questionnaire was distributed to 388 customers who indulge in online shopping to gain their preferences, perceptions, and loyalty dimensions. Results indicate that relationship-building strategies in trend that prioritize trust and personal touch have a significant positive contribution towards customer loyalty. Customized marketing, communication, trust and commitment were the preferences of each individual and therefore enhances emotional attachment with brands and increases retention levels while enhancing satisfaction. Thus, the fundamental premise of trust at the level of communication is meant to be clear and honest, thereby reducing uncertainty and building confidence in the understanding that the organization keeps its promise, thus further allegiance through the sense of belonging and reliability from consistent service quality and fulfillment of promises by the organization. The place of technology integration in shaping customer experiences extract has also been mentioned in this study. Tools such as artificial intelligence (AI) and machine learning enable the organization to provide customized marketing strategies and understand consumer behavior more thoroughly. Omnichannel engagement and valueadded services were determined as the critical ingredients of customer loyalty-increasing convenience and creating seamless shopping experience. These practical implications of the research suggest that developing personalized marketing strategies, proper communication, trust and employee training for effective customer relationship management, and the establishment of loyalty programs rewarding repeated purchases are some of the activities a business should undertake. Businesses are to practice transparency, service consistency, and, most importantly, use technology to advance with changing customer needs. This strengthens the overall contribution of the research to the literature on online customer loyalty and relationship marketing by proving established theories in this context and by providing actionable recommendations to businesses operating in this sector. The findings underscore the strategic significance of relationship marketing in driving long-term growth and competitive advantage, which will make this research valuable to academics and practitioners in the field of online retail. Keywords: Online retailing, customer loyalty, relationship marketing, personalization, trust, communication, commitment, Delhi-NCR.